Protease supplementation improves muscle function after eccentric exercise - Buford, T. W.; Cooke, M. B.; Redd, L. L.; Hudson, G. M.; Shelmadine, B. D.; Willoughby, D. S. (Medicine & Science in Sports & Exercise, 2009)
Protease supplementation has been purported to reduce the damaging effects of eccentric exercise and accelerate recovery of muscle function, possibly by regulating inflammation.